Estudo da extração do óleo de pitanga (Eugenia uniflora L.) vermelha e roxa empregando os solventes CO2 e n - propano em altas pressões - Silva, Simone Braga da (2012)
From Surinam cherry s leaves (Eugenia uniflora L.) it is possible to extract oil that has been utilized industrially, especially by cosmetics and pharmaceuticals sectors. The extraction of this oil by using conventional methods often causes the thermal degradation of its components, and an interesting alternative has been the use of supercritical extraction technology with organic solvents. In order to better evaluate the advantages of oil extracting from red and purple Surinam cherry s leaves in high pressure, the present paper aims to study this supercritical extraction by using the supercritical carbon dioxide and pressured n-propane as solvents. After drying and milling of red and purple Surinam cherry s leaves, they were underwent to oil extraction with CO2 supercritical fluids under different temperatures (50 and 60ºC) and the pressure (150 and 250 bar) and also n-propane in different temperature (30, 45 and 60ºC) and pressure conditions (40, 60 e 80 bar). The coupling of a fractionation column in supercritical fluid extraction was used to separate components of the extract. Three distinct stationeries phases were evaluated: silica, alumina and Amberlit®. The extracted oil underwent to a gas chromatography coupled to the mass spectrometry (CG-EM) for a quantitative analysis, showing the alpha-bisabolol as composed of greater interest in its industrial application. The extraction kinetics of both solvents were obtained in an experimentally way. The experimental data were adjusted appropriately to the mathematical Sovavá model.